PEMBERDAYAAN LOCAL WISDOM DALAM PENYELESAIAN KONFLIK DI KERATON SURAKARTA HADININGRAT - Sutapa Mulja Widada; Istadiyantha Istadiyantha (Journal of Law, Society, and Islamic Civilization, 2015)
Empowerment of local wisdom in conflict resolution must start with the Surakarta palace parse the source of major problems of conflict twin kings of Surakarta triggered by disputes between Kanjeng Gusti Pangeran Harya (KGPH) Hangabehi and KGPH Tedjowulan born from different mothers .The dispute about the heir to the throne of King Keraton Surakarta. In the case resolve any conflicts that occur in both conflicts over the Surakarta palace of King Twins or King palace with the Institute for Traditional Council still uses paugeran or values of the customary laws (local wisdom) in the palace . Thus, the integration values of local wisdom in the form of customary law functioned exclusively as an instrument of conflict resolution that reflects the culture of Javanese palace noble palace as well as protecting cultural heritage.